Do Macroeconomic Factors Matter for Indonesia’s Stock Market? Evidence from the Jakarta Composite Index - Anisa Eka Fitria; Esi Fitriani Komara (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
The Jakarta Composite Index (JCI) is an important indicator of Indonesia’s capital market performance and is sensitive to domestic and global macroeconomic changes. This study analyzes the effects of the BI Rate, Fed Rate, Rupiah exchange rate, inflation, and Gross Domestic Product (GDP) on the JCI during 2020–2024, covering the COVID-19 crisis and post-pandemic recovery. Using a quantitative explanatory approach, this study employs 60 monthly time-series observations collected from Bank Indonesia, the Federal Reserve, Statistics Indonesia, and the Indonesia Stock Exchange. All variables are modeled in their original observed levels to capture direct macroeconomic transmission to stock market performance. Multiple linear regression is used to test both partial and simultaneous effects. The results show that the Rupiah exchange rate has a significant negative effect on the JCI, while GDP has a significant positive effect. In contrast, the BI Rate, Fed Rate, and inflation do not show significant partial effects. Simultaneously, all variables jointly affect the JCI, with an adjusted R² of 47.9%. These findings indicate that during crisis and recovery periods, the Indonesian stock market responds more strongly to exchange rate stability and economic growth than to short-term monetary policy movements.